Differential Genetic Effects on Statin-Induced Changes Across Low-Density Lipoprotein–Related Measures. (October 2015) - Chu, Audrey Y.; Giulianini, Franco; Barratt, Bryan J.; Ding, Bo; Nyberg, Fredrik; Mora, Samia; Ridker, Paul M.; Chasman, Daniel I.
Abstract : Background—: Statin therapy influences not only low-density lipoprotein (LDL) cholesterol levels but also LDL-related biomarkers, including non–high-density lipoprotein cholesterol (non–HDL-C), apolipoprotein B, total number of LDL particles, and mean LDL particle size. Recent studies have identified many genetic loci influencing circulating lipid levels and statin-induced LDL cholesterol reduction. However, it is unknown how these genetic variants influence statin-induced changes in LDL subfractions and non–HDL-C. Methods and Results—: One hundred sixty candidate single-nucleotide polymorphisms for effects on circulating lipid levels or statin-induced LDL-cholesterol lowering were tested for association with response of LDL subfractions and non–HDL-C to rosuvastatin or placebo for 1 year among 7046 participants from the Justification for Use of Statins in Prevention: an Intervention Trial Evaluating Rosuvastatin (JUPITER) trial. Of the 51 single-nucleotide polymorphisms associated with statin response for ≥1 of the LDL subfractions or non–HDL-C, 20 single-nucleotide polymorphisms could be clustered according to effects predominantly on LDL particle size, predominantly on LDL particle number, and on apolipoprotein B but not on LDL cholesterol or non–HDL-C. Conclusions—: These differential associations point to pathways of LDL response to statin therapy and possibly to mechanisms of statin-dependent cardiovascular disease risk reduction. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00239681. Abstract : Supplemental Digital Content is available in the text.